2005
DOI: 10.1007/s10438-005-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Free and conjugated forms of salicylic acid: Their content and role in the potato

Abstract: Hydrolysis of conjugated forms of salicylic acid and accumulation of its free form was observed after infection of potato tubers ( Solanum tuberosum L.) with an incompatible race of phytophthora or treatment with an elicitor (chitosan). Infection of tubers with a compatible race of the pathogen or treatment with a suppressor (laminarin) decreased both the degree of hydrolysis of conjugated forms of salicylic acid and the accumulation of its free form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…SA is also involved in the regulation of plants’ response to stress, such as high or low temperature, salts, or oxidative conditions. In termogenic plants, SA is the natural trigger of heat production. …”
Section: Introductionmentioning
confidence: 99%
“…SA is also involved in the regulation of plants’ response to stress, such as high or low temperature, salts, or oxidative conditions. In termogenic plants, SA is the natural trigger of heat production. …”
Section: Introductionmentioning
confidence: 99%
“…A primary signaling agent for activating plant defense responses is salicylic acid (SA) [10][11][12][13][14][15][16]. Once SA accumulates to an activation threshold, a signal activates a series of defense responses, including activation of the Systemic Acquired Resistance (SAR) response [12,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…As a large part of SA is in the conjugates (Alvarez, 2000), free SA generated from its conjugates could be responsible for the small difference in levels or to none at all, that we observed at day 14. Also, it was demonstrated that conjugated forms of SA have a very weak contribution to disease resistance (Panina et al, 2005;Vasyukova and Ozeretskovskaya, 2007). The presence of free SA released from SA conjugates is unlikely to be involved in plant defence against pathogen.…”
Section: Discussionmentioning
confidence: 99%